EFEKTIVITAS MEDIA SOSIAL SEBAGAI SARANA DALAM MEMBANGUN BRAND IMAGE LV8 RESORT HOTEL CANGGU BALI - Gede Agung Putra Dalem, Anak Agung; Cindy Yohana Marcellina (Jurnal Kajian Ilmu Komunikasi, 2021)
The rapid development of technology, coupled with the existence of other media that continues to increase makes it easier for everything. Social media is of course owned by the wider community in providing and getting information. This social media also supports business actors in competing in any field, and emphasizes the use of social media to be effective in building and enhancing a brand image. The formulation of the problem in this study, how is the effectiveness of social media as a means of building the brand image of Lv8 Resort Hotel Canggu, so as to know the effectiveness of Lv8 Resort Hotel Canggu social media with a qualitative descriptive approach. Data collection was carried out by in-depth interviews with Marketing Communications and Customer at Lv8 Resort Hotel Canggu. The analysis technique used in this research is the Qualitative Descriptive Analysis Technique. From the research results, it is stated that Lv8 Resort social media is effective as a means of building a brand image